2008
DOI: 10.1177/0093854807312234
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Skills Behavior Programs for Offenders in the Community

Abstract: This study presents the findings of an evaluation of the effect on reconviction of three general offending behavior programs involving adult male offenders in the English and Welsh Probation Service. Using a quasi-experimental design controlling for population factors, there was no difference in the reconviction rates of offenders allocated to programs and a comparison group. Offenders who completed a program had a lower rate of reconviction compared to the nonstarter, noncompleter, and comparison groups. A ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 39 publications
(46 reference statements)
6
51
0
2
Order By: Relevance
“…In this analysis, the graduated with control group comparison was significant (p < .05), with the graduated group experiencing about half as many petitions (0.59) as the control group (1.21; part r = −.21). We also found that the graduate group had significantly fewer petitions and were less likely to have a petition than the dropout group, although this difference does not necessarily attest to the effectiveness of the therapy program (see Hollin et al, 2008). Results of the present study are similar to other studies on this topic.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In this analysis, the graduated with control group comparison was significant (p < .05), with the graduated group experiencing about half as many petitions (0.59) as the control group (1.21; part r = −.21). We also found that the graduate group had significantly fewer petitions and were less likely to have a petition than the dropout group, although this difference does not necessarily attest to the effectiveness of the therapy program (see Hollin et al, 2008). Results of the present study are similar to other studies on this topic.…”
Section: Discussionsupporting
confidence: 78%
“…However, many possible confounding variables were considered in the analyses, thus minimizing the effect of any possible differences between the graduated and control groups. This study was also able to obtain a nonstarter control group, which has been noted by others as a favorable alternative when the design does not allow for random assignment (Hollin et al, 2008). Another limitation includes the fact that the sample size, and especially the low percentage of females in each group, did not allow for separate analyses by sex of the participant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Conversely, those who complete treatment programs have lower reconviction rates compared to those who do not complete treatment [38]. In the current study, group non-completers were perceived by staff to be more disruptive and have more social problems than those who went on to complete the group.…”
Section: Discussionmentioning
confidence: 64%
“…Enhancing the cognitive skills of the candidates is the major objective of any educational institution, particularly a graduate health program (Greenfield and Braithwaite, 2008;Hollin et al, 2008). As a result of competitive and accreditation demands, the utilization of rapid technology, the philosophy of education, and the growing knowledge transformation have had a profound effect on the students and faculty members, particularly the social media, whether as a result of national or international requirements (Otara, 2014).…”
Section: Discussionmentioning
confidence: 99%